EKSPLORASI PENGHINDARAN PAJAK PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Lailatul Fitri Hasanah; Moh. Faisol (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2023)
The aims of this reseach to analyze the effect of profitability, leverage, liquidity, company size, and institutional ownership on tax evasion in manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2021 period. This study uses a quantitative method with a total population of 214 manufacturing companies listed on the Indonesia Stock Exchange during the 2018-2021 period. Determination of the sample using a purposive sampling method with a total sample obtained of 63 companies within 4 years so that 252 samples were obtained that met the criteria. The analysis technique in this study uses panel data analysis techniques using Eviews 12 software. The results of this study indicate that profitability, leverage, liquidity, firm size and institutional ownership have a positive and significant influence on tax avoidance simultaneously. Partial testing states that the variable profitability and firm size have a negative and significant effect on tax avoidance. Leverage has a positive and significant effect on tax avoidance. Liquidity and institutional ownership shows that there is no effect on tax avoidance. The implications of this research is that it can become a reference source for research related to tax avoidance activities and can support accounting theory, as well as consideration for companies in making decisions to determine company strategy so that they can compete globally in the future.